Parental thoughts after the Codroipo case: the other side of the story - Brunelli, L.; Romanese, F.; Tricarico, P.; Murati, A.; Benetollo, P. P.; Iob, A.; Forgiarini, M.; Valent, F.; Brusaferro, S. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. To address vaccine hesitancy and to build public trust, many factors need to be considered in the process of planning consistent public health interventions. After uncertain vaccinations of the Codroipo case, hesitant parents were surveyed about own beliefs and trusted sources of information. Methods. A semi-structured phone survey was conducted between December 2017 and February 2018, collecting also age and educational level of respondents. Results. The most trusted sources of information of the 258 surveyed parents were pediatricians (27.2%), general practitioners (25.4%) and institutional channels (12.1%). Highly educated parents trusted self-study of the scientific literature and expressed doubts about vaccine effectiveness more than others (p=0.0018). Conclusion. Despite the underlying improper vaccination issue undermined public trust, healthcare professionals and institutional channels maintained their role as trusted sources of information. Educational patterns emerged among doubtful parents should be considered by public health policies to effectively tackle vaccine hesitancy.